2007
DOI: 10.1063/1.2756522
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy in arrays of Ni, CoFeB, and Ni/Cu nanowires

Abstract: An effective field model based on intrawire and interwire dipolar interactions has been developed in order to describe the magnetic anisotropy in arrays of homogeneous and multilayer nanowires. Variable angle ferromagnetic resonance (FMR) and vibrating sample magnetometry (VSM) characterization techniques were used to determine the effective interaction field acting on Ni, CoFeB, and Ni/Cu nanowires. FMR spectra are well described by a rigid magnetization model and VSM data are in rough agreement with a mean l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 17 publications
4
49
0
2
Order By: Relevance
“…17). Good agreement (Béron et al, 2008b) was found between the experimental ΔH u values of uniform nanowires (Figs 13-14a) and the predicted values of interaction field at saturation from a micromagnetic model and from an effective field model (Carignan et al, 2007). …”
Section: Axial Applied Fieldsupporting
confidence: 55%
See 3 more Smart Citations
“…17). Good agreement (Béron et al, 2008b) was found between the experimental ΔH u values of uniform nanowires (Figs 13-14a) and the predicted values of interaction field at saturation from a micromagnetic model and from an effective field model (Carignan et al, 2007). …”
Section: Axial Applied Fieldsupporting
confidence: 55%
“…The non-magnetic metal is kept dilute in the solution to avoid excessive inclusion in the magnetic layer. Ni/Cu nanowires were fabricated by this method (-1 V for Ni, -0.56 V for Cu), varying the Cu/Ni ratio from 0.3 to 1.17 (Carignan et al, 2007). …”
Section: Fabrication Of Nanowire Arraysmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of this easy-plane shape anisotropy was demonstrated through the use of a simple macrospin theoretical model in Ref. 46. The presence of the easy-plane shape anisotropy in MNWAs was also described in Refs.…”
Section: Introductionmentioning
confidence: 99%